Isolation and identification of culturable aerobic halophilic Archaea associated with salt crystals from Urmia Lake - Gholamreza Zarrini; Rana Rahmani; Manica Negahdaripour; Miald Mohkam; Younes Ghasemi (Shiraz University of Medical Sciences, 2018)
Urmia Lake is one of the largest hypersaline lakes in the world. Water evaporation and saturation cause a lot of salt crystals formation on the lake beach. In this study, extremely halophilic strains were isolated from salt crystals that formed in distinct regions of lake. The isolation was performed by means of modified Marine agar medium and their DNA were extracted and amplified by PCR using universal primers that amplify archaeal 16S rDNA. The amplified archeal DNA fragments were purified, and were subjected to 16S rRNA gene sequencing analysis which was compared to known sequences by a Blast search at NCBI (National Center for Biological Information). Similarity analysis based on 16S rRNA gene sequences of all isolates indicated that the archaeal isolates belong to three different halophilic genera of euryarcheota: Halorubrum, Haloarcula and Halobacterium. These extreme halophilc archaea can be used as a potential source of new therapeutic metabolites and enzymes as well as antibiotic compounds along with novel biotechnological applications.